Natural antioxidants and lipid profile improvement in lamb meat products - Carvalho, Francisco Allan Leandro de (2020)
This study evaluated the effect of reformulation (fat substitution and use of natural antioxidants) on lamb meat products during refrigerated storage: (i) lamb burger with enhanced lipid profile and extracts of guarana seed and pitanga leaf as natural antioxidants; (ii) cooked animal fat-substituted sausages with flaxseed, olive and chia oils; and (iii) fresh lamb sausage with improved lipid profile and different levels of turmeric extract. Physico-chemical, sensory and oxidative stability characteristics were evaluated during their shelf life. Analyzes included proximate composition (moisture, protein, fat and ash) and sensory acceptance (day 0); pH, color (L *, a *, b *), TBARs, carbonyl content and visual sensory evaluation (0, 6, 12 and 18 days for burgers and fresh sausages and 0, 30, 60 and 90 for cooked sausage); fatty acids and volatile compounds profile (0 and 18 days in burgers and 0 days in cooked sausages), and DPPH (0, 6, 12 and 18 days in burgers and fresh sausages). The guarara seed and pitanga leaf extracts showed higher antioxidant activity to protect of hamburgers against lipid and protein oxidation during the storage time than the synthetic antioxidant, without compromising the chemical and sensory characteristics of lamb hamburger. Vegetable oils provided consistent improvements in fatty acid profile and nutritional indexes of cooked lamb sausages; mainly chia and flaxseed. However, sausages made with chia oil showed a loss in texture parameters and sensory analysis. On the other hand, flaxseed oil was able to improve the lipid profile of sausages without changing its technological and sensory characteristics. Turmeric extract showed higher antioxidant capacity during storage and, consequently, promoted lower lipid oxidation, confirmed by the results of TBARs and lower formation of volatile compounds derived from oxidation, even at a lower dose than synthetic antioxidant. Thus, guarana seed extracts and pitanga leaves can replace the synthetic antioxidant in lamb burgers without causing detrimental changes in their physicochemical and sensory properties. Among the oils tested, flaxseed oil is most recommended as a fat substitute in cooked lamb sausages. Turmeric Extract is a promising natural antioxidant to extend the shelf life of fresh lamb sausages with improved lipid profile without compromising its quality characteristics.